The Discourse and its References in Maha Hassan's Novels - Selected Models (Raparin Journal of Humanities (RJH), 2023)
This research was written under the title (The Discourse and its References in Maha Hassan's Novels - Selected Models). It aims at clarifying the concept of discourse and its references in the works of the Syrian-Kurdish novelist (Maha Hassan). This topic has been chosen due to the fact the previous studies have  not tackled the mechanism of discourse formation and its references in the work of this novelist, and her vision of the world that she conveyed to us through narrative discourse techniques, including: the narrator and his/her listener, which are studied in this research.The importance of the research lies in addressing topics relating to Man and our  Modern Age including: migration, women, identity, sense of belonging, center and margin, and others. In this study, the researcher draws on the (formative structuralist) approach, which links literature to the product and society, and shows the dialectical relationship between narrative discourse and society.  It also focuses on the relationship of the artistic structure of the literary work with reality and social awareness because the novel as a literary work, particularly that of Maha Hasan’s, is closely related to society and its transformations. In conclusion, the researcher arrived at several results, including: there is a clear difference in the experiences of (Maha Hassan) as a novelist in Syria and in France. Migration provided her with a suitable atmosphere to reveal her Kurdish identity, and it also provided her with the freedom to express her vision to the public, and to express her feminist bias.